Introgression of a novel cold and drought regulatory‐protein encoding CORA‐like gene, SbCDR, induced osmotic tolerance in transgenic tobacco. Issue 2 (2nd December 2020) - Jha, Rajesh Kumar; Patel, Jaykumar; Patel, Manish Kumar; Mishra, Avinash; Jha, Bhavanath
Abstract: A potent c old and d rought r egulatory‐protein encoding gene, SbCDR was cloned from an extreme halophyte Salicornia brachiata . In vitro localisation study, performed with SbCDR :: RFP gene‐construct revealed that SbCDR is a membrane protein. Overexpression of the SbCDR gene in tobacco plants confirmed tolerance against major environmental constraints such as salinity, drought and cold, as evidenced by improved chlorophyll contents, plant morphology, plant biomass, root length, shoot length and seed germination efficiency. Transgenic lines also exhibited high accumulation of proline, total sugar, reducing sugar, free amino acid and polyphenol, besides the low level of malondialdehyde (MDA) contents. SbCDR transgenic lines showed better relative water contents, membrane stability index and osmotic water potential. Furthermore, higher expression of ROS scavenging genes was observed in transgenic lines under stress. Moreover, microarray analysis revealed that several host genes were upregulated and downregulated under drought and salt stress conditions in SbCDR transgenic line compared with control (WT) plants. The results demonstrated that the overexpression of the halophytic SbCDR gene has intense effects on the abiotic stress tolerance of transgenic tobacco plants. However, the exact mode of action of SbCDR in multiple abiotic stress tolerance of plants is yet to be unveiled. It is believed that the precise role of SbCDR gene will provide additional information to comprehend the abiotic stress tolerance mechanism. Furthermore, it will appear as a promising candidate gene for improving stress tolerance in different crop plants for sustainable agriculture and crop productivity.